TRANSFORMATIONS IN A LITTLE PRINCESS MOVIE: AN ADAPTATION ANALYSIS - L Dyah Purwita Wardani; Fina Rifqiyah; Dina D. Kusumayanti (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2021)
A Little Princess is a novel written by Frances Hodgson Burnett (1905). This novel has been adapted several times into film, one of which is Alfonso Cuaron's (1995) work produced by Warner Bross Picture. This film was released in 1995 with the same title, "A Little Princess". This article focuses on the motives and ideologies of the adaptation process from novel to film. The changes that occur are a consequence of using media that change from text to screen scenes. This study will compare the intrinsic elements contained in novels and films. This research will also discuss how the transformation from novel adaptation to film and the motives. The adaptation theory by Linda Hutcheon (2006) was used to analyze the motives of adapting novels to films and will be supported by the theory of Mythology by Roland Barthes' (1957) to find ideology. Barthes' semiotic analysis helps the writer find the hidden ideology in the adaptation work, leading us to find the motive of the transformation process. As a result, the adaptation work of Alfonso Cuaron shows the existence of an ideology of feminism and American values. This ideology exists because of the cultural and political motives of the filmmaker to gain benefit from the process of adaptation. Keywords : adaptation, ideology, myth, motives.